2020
DOI: 10.7554/elife.62307
|View full text |Cite
|
Sign up to set email alerts
|

Translation in amino-acid-poor environments is limited by tRNAGln charging

Abstract: An inadequate supply of amino acids leads to accumulation of uncharged tRNAs, which can bind and activate GCN2 kinase to reduce translation. Here, we show that glutamine-specific tRNAs selectively become uncharged when extracellular amino acid availability is compromised. In contrast, all other tRNAs retain charging of their cognate amino acids in a manner that is dependent upon intact lysosomal function. In addition to GCN2 activation and reduced total translation, the reduced charging of tRNAGln in amino-aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 43 publications
1
38
0
Order By: Relevance
“…We next asked why collagen production in TGFβ-stimulated fibroblasts was impaired when the extracellular glutamine concentration was reduced. Based on a recent report suggesting that glutamine-tRNA is often uncharged when cells are cultured in low amino acid medium 20 , we used a qPCR-based method to analyze the charging state of tRNAs for several non-essential amino acids (NEAAs) and leucine-tRNA as control. We observed a profound uncharging of glutamine-tRNA in TGFβ- but not mock-treated NIH-3T3 cells cultured in low Gln ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We next asked why collagen production in TGFβ-stimulated fibroblasts was impaired when the extracellular glutamine concentration was reduced. Based on a recent report suggesting that glutamine-tRNA is often uncharged when cells are cultured in low amino acid medium 20 , we used a qPCR-based method to analyze the charging state of tRNAs for several non-essential amino acids (NEAAs) and leucine-tRNA as control. We observed a profound uncharging of glutamine-tRNA in TGFβ- but not mock-treated NIH-3T3 cells cultured in low Gln ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These data suggest that an inability to maintain glutamine tRNA charging could lead to activation of GCN2 and reduced translation in fibroblasts treated with TGFβ in a low glutamine environment, resulting in a reduction of ECM synthesis. Glutamine-tRNA charging has been reported to be restored in proliferative fibroblasts by inhibiting glutaminase with the allosteric inhibitor CB839 20 . However, CB839 treatment did not rescue GCN2 activation induced by TGFβ treatment in low Gln and only marginally increased collagen I protein levels ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the reduced availability of amino acids results in an accumulation of uncharged tRNAs, which can bind and activate the kinase GCN2. GCN2 phosphorylates eIF2a, preventing eIF2 from being recycled to the GTP-bound state required for translation initiation and thus inhibiting global protein synthesis [72,73]. Whether GCN2 plays a major regulatory role in controlling global protein synthesis in T cells and is a major signaling factor through which amino acid deprivation controls the T cell response are unclear.…”
Section: Regulators Of the Protein Synthesis Rate In T Cellsmentioning
confidence: 99%
“…Several recent studies have indicated the potential of tRNAs to serve as a critical capacitor of metabolic information. 40, 41 Evaluating whether oncometabolites can modulate endogenous tRNA modification levels - and what affect this has on cancer development - represents an important topic for future inquiry. Finally, we note with interest the parallels between the fumarate-dependent synthetic lethal mechanism invoked above and the ‘collateral vulnerability’ concept pioneered by Muller and coworkers.…”
Section: Discussionmentioning
confidence: 99%